The Effect of Filler Content on Mechanical Properties of Polypropylene/Clay Nanocomposites - Teuku Rihayat; Pocut Nurul Alam (Jurnal Rekayasa Kimia & Lingkungan)
This study investigated the effect of filler content on mechanical properties of polypropylene. There are synthesis clay and un-synthesis clay used as filler content. Different ratio of clay in polypropylene to study which ratio has a better mechanical property. The tensile test was carried out using INSTRON5565 and the maximum stress, strain, and modulus of elasticity observed. The experimental results showed that polypropylene/clay nanocomposite has a higher maximum stress compare to pure polypropylene and un-synthesis clay. Besides that modulus of elasticity of specimen calculated and finds that it increased with increment filler content and strain did not affect by filler. The synthesis clay filled into polypropylene will have a better mechanical property.